Pendidikan Karakter Dalam Proses Pembelajaran Matematika - Alga, Riska Kalidya; Azhara, Selvyra; Hsb, Azka Amalia Ashari; Hakim, Emi Herliza; Sarlina, Shavika; Hasibuan, Intan Syhara; Siregar, Lailatun Nur Kamalia (Khazanah : Journal of Islamic Studies, 2023)
In this instance, learning occurs outside of the traditional classroom setting through remote online learning, which offers instructors additional duties and responsibilities in addition to challenges in developing students' character. The study's goal is to explain character education as it relates to math instruction in schools. Qualitative research methodology is used. In this study, documentation, literature reviews, observation, and interviews were employed as data collection methods. This study's data analysis consists of data reduction, data visualization, conclusion, and verification. The research's conclusions center on the following ideals, which are fostered when students study mathematics in Class V at SDIT Private Al Irsyad Medan: 1) Spiritual, 2) Orderly, 3) Accountable, 4) Precise, 5) Ingenious, 6) Truthful, 7) Honorable, 8) Curiosity, and 9) Confidence. Character education in Mathematics learning in Class V SDIT Swasta Al Irsyad Medan is applied by integrating character values in curriculum content that has been formulated into learning, especially in RPP.